Master tracks in different resolutions during POLAR 5 campaign AIRMETH_2016 - Daniel Steinhage (PANGAEA, 2017)
This dataset was created via processing of raw position data acquired by the GPS sensor for scientific equipment on Polar 6/Polar 5 to receive a validated master track which is used as reference of further expedition data.